2018
DOI: 10.1155/2018/2074021
|View full text |Cite
|
Sign up to set email alerts
|

3D Culture of Bone Marrow-Derived Mesenchymal Stem Cells (BMSCs) Could Improve Bone Regeneration in 3D-Printed Porous Ti6Al4V Scaffolds

Abstract: Mandibular bone defect reconstruction is an urgent challenge due to the requirements for daily eating and facial aesthetics. Three-dimensional- (3D-) printed titanium (Ti) scaffolds could provide patient-specific implants for bone defects. Appropriate load-bearing properties are also required during bone reconstruction, which makes them potential candidates for mandibular bone defect reconstruction implants. However, in clinical practice, the insufficient osteogenesis of the scaffolds needs to be further impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…However, despite such a short time, after postmortem examination, it can be concluded that the scaffolds with injected cells have become more integrated with the skull bones than the empty skeleton alone, which may result from the formation of cartilage, impossible to visualize in computed tomography. Similar results were described for maxillary sinus elevation with different bone substitutes and BMSCs [38], although the low survival rate of grafted BMSCs was reported, which resulted from acute inflammation and mechanical damage [39] and indisposed to use the therapy in a clinic.…”
supporting
confidence: 66%
“…However, despite such a short time, after postmortem examination, it can be concluded that the scaffolds with injected cells have become more integrated with the skull bones than the empty skeleton alone, which may result from the formation of cartilage, impossible to visualize in computed tomography. Similar results were described for maxillary sinus elevation with different bone substitutes and BMSCs [38], although the low survival rate of grafted BMSCs was reported, which resulted from acute inflammation and mechanical damage [39] and indisposed to use the therapy in a clinic.…”
supporting
confidence: 66%
“…In addition to collagen, poly( l -lactic acid) and blends of these materials, Matrigel, a hydrogel mainly composed of type IV collagens, entactin, perlecan and laminin has been shown to increase the osteogenic differentiation potential compared to 2D cell culture. If differentiated within a Matrigel scaffold, human BM-MSCs showed higher activity of alkaline phosphatase (an early marker of osteogenesis) compared to the 2D counterparts [ 90 ]. In addition, Alizarin Red S staining revealed higher Ca 2+ deposition in cells differentiated in 3D.…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
“…tubular complex structures in the presence of proper angiogenic and extracellular matrix mediators (Shen et al, 2015;Yu et al, 2018). To evaluate the involvement of TNFR2 in this regenerative feature, WT and TNFR2 KO-MSCs were cultured on Matrigel using either DMEM standard medium or EC growth medium (EGM2) containing a variety of pro-angiogenic FIGURE 4 | The expression of TNFR2 by mesenchymal stem cells (MSCs) is correlated to their higher NO production.…”
Section: Expression Of Tnfr2 By Mesenchymal Stem Cells Influences Thementioning
confidence: 99%